Interview with Carlos Soria. Journalists experience a crisis of passion - Rodriguez, Jorge (2022)
More than one interview was a conversation. Fluid and passionate. Carlos Soria Saiz, founder and vice president of Innovation International Media Consulting Group, the prestigious international newspaper consultant first division landed in Piura, Peru with a single reason: to attend the ceremony of the honorary doctorate by the Faculty Communication at the University of Piura to his teacher, the legendary professor of law lnformation of the Complutense of Madrid, Jose Maria Desantes Guanter.An invitation to take a very cold lemonade to quench the soporific heat of Piura served as a pretext to talk about what Soria knows best: the Latin American journalism.